A Systems Model of Repeat Court-Ordered Removals: Responding to Child Protection Challenges Using a Systems Approach. (20th May 2020) - Wise, Sarah
Abstract: Repeat removals, where parents lose successive infants and children to out-of-home care, is a systems problem requiring a systems approach to broaden our thinking and expand our choices for action. A transdisciplinary group of key stakeholders in Australia jointly constructed a causal loop diagram to bring forth the systemic structure underlying the issue and identify system conditions that need to be altered. Analysis of the causal loop diagram surfaced eight dynamic positive feedback loops which result in a self-reinforcing system. While the model reflects the understanding of a relatively small group and requires further testing, it adds to current conceptualisations of repeat removal by hypothesising systemic causes and offers new directions for prevention. Stakeholders homed in on stigmatised stereotypes of recurrent birth mothers and the child protection culture, practitioner decision-making, parent–practitioner interactions and parental participation in child protection case planning as ways of correcting against vicious feedback loops. A systems approach contributed useful insights into the problem of repeat removals and could productively be used in respect of a range of other complex child protection challenges.